Predicting Narrative Essay Writing Ability through Grammar Awareness and Critical Thinking Skills: Evidence from Indonesian EFL Vocational High School Students - Aqila Thahira Sisfiamuhsha; Ismalianing Eviyuliwati; Alek Alek; Gelar Dwirahayu (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2026)
This exploratory study examined the relationships among grammar awareness, critical thinking skills, and narrative essay writing ability among Indonesian EFL vocational high school students. Using a quantitative correlational design, data were collected from 35 tenth-grade students in one intact class at a vocational high school in Tangerang, selected through purposive sampling, using a grammar awareness test, a critical thinking test, and a narrative essay writing task, all validated through expert judgment and empirical testing. Data were analyzed using Pearson Product-Moment Correlation and Multiple Linear Regression. The results indicated significant positive correlations between grammar awareness and narrative writing ability (r = .649, p < .01) and between critical thinking skills and narrative writing ability (r = .687, p < .01). Grammar awareness and critical thinking skills jointly predicted narrative essay writing ability, explaining 54% of the variance (R² = .540, Adjusted R² = .511), with critical thinking emerging as the stronger predictor (β = .458) compared to grammar awareness (β = .347). Given the limited sample drawn from a single intact class, these findings should be interpreted as exploratory evidence rather than a broad generalization. Nonetheless, the results suggest that effective narrative writing draws on both linguistic competence and higher-order thinking skills. Accordingly, EFL writing instruction at the vocational level may benefit from integrating grammar instruction with activities that foster critical thinking.